Impact of Microfinance Institutions on Scaling Micro Enterprises in the Kathmandu Valley - Tandukar, Nikhil; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2025)
This study examines the impact of microfinance institutions on scaling micro enterprises in the Kathmandu Valley. Growth of micro enterprise is the dependent variable. The selected independent variables are micro credit, training programs, financial advisory, interest rate, marketing facility, technical support and business idea generation. The primary source of data is used to assess the opinions of respondents regarding micro credit, training programs, financial advisory, interest rate, marketing facility, technical support, business idea generation, and growth of micro enterprise. The study is based on both primary and secondary data. The primary data were gathered from 194 respondents through questionnaires. The secondary data were gathered from National Economic Census. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of microfinance institutions on micro enterprises in the Kathmandu Valley. The study showed a positive impact of micro credit on growth of micro enterprises. It indicates that higher the micro credit, higher would be the growth of micro enterprises. Similarly, the study showed a positive impact of training programs on growth of micro enterprises. It indicates that higher the training program for increasing awareness towards microenterprises lead to increase in growth of micro enterprises. Likewise, the study also revealed a positive impact of technical support on growth of micro enterprises. It indicates that higher the technical support from the concern authority leads to increase in growth of micro enterprises. Further, the study observed a positive impact of marketing facilities on growth of micro enterprises. It indicates that supportive marketing facilities lead to increase in growth of micro enterprises. In addition, the study observed a positive impact of financial advisory on growth of micro enterprises. It indicates that proper financial advices from the concerned authority leads to increase in growth of micro enterprises. Likewise, the study showed a negative impact of interest rate on growth of micro enterprises. It indicates that higher the interest rate, lower would be the growth of micro enterprises. Further, the study also revealed a positive impact of business idea generation on growth of micro enterprises. It indicates that different business ideas related to microenterprises lead to increase in growth of micro enterprises.